Factores que influyen en la calidad de vida de los usuarios del proyecto “Atención Domiciliaria para Personas Adultas Mayores sin Discapacidad”, Santa Rufina, periodo actual - Román Yaguana, Gina Mercedes (2025)
The factors that influence the quality of life of older adults is a social problem that has negatively impacted this population group, their families and the community in general. The research conducted with the users who belong to the project “Home Care for Elderly People without Disabilities”, was aimed at identifying the factors that predominantly influence their quality of life, for this purpose, objectives were set as a theoretical and methodological basis for the different factors, also, seeks to analyze them to see how they influence their quality of, life and in turn propose alternative solutions from the intervention of Social Work focused on strengthening family ties to improve the quality of life of its users. Therefore, the methodology applied in this study has a mixed approach (qualitative and quantitative), cross-sectional, in older adults of Santa Rufina parish who belong to the Home Care for the Elderly without Disabilities project. For this purpose, structured and semi-structured interviews were conducted, through which it was determined that 61 % of the older adults have a moderate quality of life, followed by 30 % who have a low quality of life, which has been affected by the economic and environmental factors. In short, there are factors that influence the quality of life of older adults in a positive way, such as social factors, and in a negative way, such as family, environmental and socioeconomic factors, which affect their well-being